SELECTION OF NEW PROMISING SEEDLESS MANDARINS TRIPLOID HYBRIDS FROM CROSSES BETWEEN MONOEMBRYONIC DIPLOID FEMALE AND DIPLOID MALE PARENTS - HAMID BENYAHIA, HANDAJI NAJAT; HASSAN BENAOUDA, NAJAT ARSALANE (Research in Biotechnology, 2017)
Morocco is one of the major exporters of small citrus fruits, such as mandarin and Clementine. Seedlessness is a major criterion for this horticultural group. The present study focused on the selection of the best triploid mandarin hybrids (2n=3x=27) characterized by seedless fruits. A series of crosses between ‘Sidi Aissa’ clementine (female parent) and seven mandarin varieties (‘Lee’, ‘Wilking’, ‘Osceola’, ‘Carvalhal’, ‘Satsuma Frost’, ‘Satsuma Owari’ and ‘Chienka’) was performed by the National Institute for Agricultural Research. Forty triploid mandarins were obtained and planted since 2002 in an experimental field at El Menzeh. Varietal evaluation was focusing on fruit quality traits during seven years. Statistical analyzes showed that there is a significant difference for all studied characters and between hybrids. The number of seeds per fruit is the main criterion which differentiates between triploids mandarin’s hybrids and their diploid parent “clementine Sidi Aissa”. The best hybrids selected were: HT11, HT13, HT27, HT43, HT44, and HT49. The best crosses are C1 (‘Sidi Aissa’ × ‘Wilking’) andC2 (‘Sidi Aissa’ ×‘Osceola’). These promising triploid hybrids of mandarin have been multiplied on several rootstock trials and are in the process of quantitative evaluation and multi-site testing.